Effect of Harvest Time on Seed Composition, Keeping Quality and Germination of Groundnut (Arachis Hypogaea L.) Var. Matjam - Abdul, M. Teng (1992)
Differences in seed maturity during harvest have been a conmon problem in groundnut. The present study was conducted to look into different factors in order to obtain viable information that could define optimum harvest for Mat jam groundnut. These characters include: (a) percentage of nature pods per 100 pads, (b) weight of kernels per plant, (c) oil, protein, and carbohydrate contents, (d) keeping quality, and (e) germination rate. The groundnut was grown in the field in 1986 and 1987 and harvested at 17 different harvest dates from 68 days after planting (DAP) to 100 DAP. The percentage of mature pods per 100 pods in both years was about 65.6% at 88 DAP. Later harvests did not show significant increase in percentage of mature pods. Highest kernel weight of 8.18 g/plant was obtained at 100 DAP but was not significantly different from the 92 and 96 DAP with 7.78 am 6.55 g/plant, respectively. The number of nodes on the main axis between 88-96 DAP ranged from 26 to 28. This plant character was easy to identify and to count because even when the leaves had fallen, the scars could still be seen.